2002
DOI: 10.1172/jci16001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ABCG5 and ABCG8 promotes biliary cholesterol secretion and reduces fractional absorption of dietary cholesterol

Abstract: Two ATP-binding cassette (ABC) transporters, ABCG5 and ABCG8, have been proposed to limit sterol absorption and to promote biliary sterol excretion in humans. To test this hypothesis, a P1 clone containing the human ABCG5 and ABCG8 genes was used to generate transgenic mice. The transgenes were expressed primarily in the liver and small intestine, mirroring the expression pattern of the endogenous genes. Transgene expression only modestly affected plasma and liver cholesterol levels but profoundly altered chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
324
3
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(345 citation statements)
references
References 39 publications
15
324
3
3
Order By: Relevance
“…Cholesterol secretion is one of the mechanisms by which the liver excretes cholesterol. Because the sterol transporters ABCG5 and ABCG8 mediate cholesterol secretion into bile 21,22,31 , plant sterols have been thought to up regulate the expression of these two genes in the liver and thus cholesterol excretion, thereby lowering plasma cholesterol concentrations. Paradoxically, the present study showed that stanol esters (0·7 % in the diet) decreased liver ABCG5 mRNA levels and appeared to lower ABCG8 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol secretion is one of the mechanisms by which the liver excretes cholesterol. Because the sterol transporters ABCG5 and ABCG8 mediate cholesterol secretion into bile 21,22,31 , plant sterols have been thought to up regulate the expression of these two genes in the liver and thus cholesterol excretion, thereby lowering plasma cholesterol concentrations. Paradoxically, the present study showed that stanol esters (0·7 % in the diet) decreased liver ABCG5 mRNA levels and appeared to lower ABCG8 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ABCG5 and ABCG8 transporters in cholesterol efflux has further been demonstrated in transgenic mice by expressing both human and mouse ABCG5 and ABCG8 genes. Results showed approximately 50 % reductions in cholesterol absorption and marked increases in biliary cholesterol secretion and faecal neutral sterol excretion compared with their wild-type littermates 22 . In contrast, the ABCG5-/-and ABCG8-/-mice presented increased absorption of dietary sterols and impaired biliary * Corresponding author: Dr Peter J. H. Jones, fax þ1 204 474 7552, email peter_jones@umanitoba.ca Abbreviations: Ch-Con, control diet with 0·25 % cholesterol; Con, control diet; Sta, Ch-Con diet with 1 % plant stanols; Ste, Ch-Con diet with 1 % plant sterols; SteF, sterols esterified to fish oil; StaA, stanols esterified to ascorbic acid.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These are members of the large ABC family of transmembrane proteins, 40 and were recently shown to be essential for cholesterol efflux from the liver to the bile canaliculus and from the intestine. 41 The ABC transporters have also been implicated in mediating estrogen actions on cholesterol transport. 42,43 In mice, although no direct assessment of the effects of estrogen on ABC transporters has yet been reported, one study 26 had suggested that ABCG5/G8 are not modulated by estrogen in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were washed thrice in TTBS and incubated with horseradish peroxidase-conjugated V. W. Bloks et al: Down-regulation of hepatic and intestinal Abcg5 and Abcg8 expression associated 105 secretion of cholesterol into bile is coupled to that of phospholipids in a process that is, in part, controlled by bile salt secretion [6]. Recent studies, however, indicate that specific ABC transporters, i.e., Abcg5 and Abcg8, are involved in biliary cholesterol secretion [7,8]. The genes encoding these transporters are highly expressed in the liver [9].…”
mentioning
confidence: 99%